Metabolic Fatty Liver Disease in Children: A Growing Public Health Problem - Sébastien Le Garf; Véronique Nègre; Rodolphe Anty; Philippe Gual (Biomedicines, 2021)
Metabolic-associated fatty liver disease (MAFLD), previously called nonalcoholic fatty liver diseases (NAFLD), is one of the most important causes of chronic liver disease worldwide and will likely become the leading cause of end-stage liver disease in the decades ahead. MAFLD covers a continuum of liver diseases from fatty liver to nonalcoholic steatohepatitis (NASH), liver fibrosis/cirrhosis and hepatocellular cancer. Importantly, the growing incidence of overweight and obesity in childhood, 4% in 1975 to 18% in 2016, with persisting obesity complications into adulthood, is likely to be harmful by increasing the incidence of severe MAFLD at an earlier age. Currently, MAFLD is the leading form of chronic liver disease in children and adolescents, with a global prevalence of 3 to 10%, pointing out that early diagnosis is therefore crucial. In this review, we highlight the current knowledge concerning the epidemiology, risk factors and potential pathogenic mechanisms, as well as diagnostic and therapeutic approaches, of pediatric MAFLD.